Cytotoxic of Ethanol Extract of Leaves and Bark Mareme (Glochidion Arborescens Blume.) Against 4T1 Cancer Cells - Haryoto, Haryoto; Saputri, Luki Rahmadani Tulus (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Mareme plant (Glochidion arborescens Blume.) is a plant that has the potential to treat cancer. In a study on the leaves and bark of the Mareme (Glocidion arborescens Blume.) plant, tests for antioxidant, antidiabetic, and anti-inflammatory activities were previously carried out. Secondary metabolites that play a role in cytotoxic activity in Mareme plants are flavonoids, and these compounds can specifically kill the progression of cancer cells. This study aims to determine the content of compounds, examine cytotoxic activity, and determine the percentage of living cells in the leaves and bark of Mareme (Glochidion arborescens Blume.). The leaves and bark of Mareme (Glochidion arborescens Blume.) were extracted by maceration using a 96% ethanol solvent, then identification of the compounds was carried out to determine the content contained in the ethanol extract of the leaves and stem bark of Mareme, and then a cytotoxic test was carried out using the MTT assay method. The compounds contained in Mareme leaves are flavonoids, tannins, steroids, saponins, and polyphenolics, while the chemical compounds in Mareme stem bark are flavonoids, tannins, saponins, and polyphenolics. Tests were carried out at concentrations of 500, 600, and 800 µg/mL. The results of the cytotoxic test showed that the value of live cells in the ethanol extract of Mareme leaves (Glochidion arborescens Blume.) was 114.21, 106.21, and 78.91%, respectively. While the value of live cells in the ethanol extract of Mareme stem bark (Glochidion arborescens Blume.) was 59.56, 56.37, and 42.85%, respectively. The higher the concentration, the smaller the living cells produced.